THE INFLUENCE OF LIVE STREAMING AND CUSTOMER REVIEWS ON PURCHASING DECISIONS FOR KEMAIU SHAMPOO PRODUCTS - Purba, Ruth Agita; Mandasari, Virginia (International Journal of Multidisciplinary Research and Literature, 2024)
This study aims to find how much influence live streaming and customer reviews have on purchasing decisions for "Kemaiu" brand shampoo products. Where in this study Live streaming is considered an innovative and interactive marketing tool, while customer reviews provide views from direct experience with the product. The results of data analysis show that live streaming and customer reviews significantly influence purchasing decisions for Kemaiu shampoo products. Viewers of live streaming tend to have a positive perception of the product after seeing a live demonstration and interacting with the live streaming organizer. Customer reviews, particularly those reflecting satisfaction and product performance, provide strong confirmation of the quality and benefits of Kemaiu shampoo